Asas Psikologis dan Implikasinya Dalam Pendidikan Agama Islam Perspektif Hasan Langgulung - Suminto Suminto (ANDRAGOGI, 2020)
AbstractThe psychological principle of Islamic education becomes very important in its own, considering it can be understood as the truth that is a foothold or basic thinking, both in the planning, implementation, or evaluation of education based on the theories of psychology. In addition, understanding the education in it also contains principles as a place and an upright footing, upright in matter, upright in interaction, upright in innovation, or upright in dreams. The type of research used is library research. The analysis of content or content analysis is used as a method of analysis in this study. The results of this study contained the basic concept of psychological in Islamic education according to Hasan Langgulung and the implications of the basic psychological concept in the education of Islamic agam. Therefore, in the process of education should pay attention to the development of the soul, as well as the physical growth of the students by referring to the basis, objectives, curriculum, materials, and evaluation that brings human function as ' abid and the fil decorated with righteous charity.Keywords: Principles Of Psychological, Islamic Education, Hasan LanggulungAbstrakAsas psikologis dalam pendidikan Islam menjadi sangat penting keberadannya, mengingat dapat difahami sebagai kebenaran yang menjadi pijakan atau dasar berpikir, baik pada tahap perencanaan, pelaksanaan, maupun evaluasi  pendidikan yang berdasarkan atas teori- teori dari psikologi. Selain itu, memahami pendidikan di dalamnya juga terdapat asas-asas sebagai tempat dan pijakan yang tegak, tegak dalam materi, tegak dalam interaksi , tegak dalam inovasi, atau tegak dalam cita-citanya. Jenis penelitian yang digunakan adalah penelitian kepustakaan  atau library research. Adapun analisis isi atau content analysis digunakan sebagai metode analisis dalam penelitian ini. Hasil penelitian ini memuat tentang konsep asas psikologis dalam pendidikan Islam menurut Hasan Langgulung dan implikasi dari konsep asas psikologis dalam pendidikan agam Islam. Oleh karenanya, dalam proses pendidikan harus memperhatikan perkembangan jiwa, maupun pertumbuhan raga peserta didik dengan mengacu pada dasar, tujuan, kurikulum, materi, serta  evaluasi yang membawa fungsi manusia sebagai ‘abid dan khalifatullah yang dihiasi dengan amal saleh.Kata Kunci: Asas Psikologis, Pendidikan Islam, Hasan Langgulung